Cloning and expression in Escherichia coli of histidine utilization genes from Pseudomonas putida. - Consevage, M W (1985)
A library of the Pseudomonas putida chromosome, prepared through the use of the cosmid pJB8 ligated to a partial Sau3A digest of bacterial DNA, followed by in vitro packaging into bacteriophage lambda particles, was used to construct a strain of Escherichia coli which contained the genes for histidine utilization. This isolate produced a repressor product and all five enzymes required in Pseudomonas spp. for histidine dissimilation, whereas none of these could be detected in the nontransduced parent E. coli strain. When this transductant was grown on various media containing histidine or urocanate as the inducer, it was observed that production of the cloned histidine degradative enzymes was influenced somewhat by the choice of nitrogen source used but not by the carbon source. The recombinant cosmid was isolated and found to consist of 21.1 kilobase pairs of DNA, with approximately 16 kilobase pairs derived from Pseudomonas DNA and the remainder being from the pJB8 vector. Digestion of this insert DNA with EcoRI provided a 6.1-kilobase-pair fragment which, upon ligation in pUC8 and transformation into an E. coli host, was found to encode histidine ammonia-lyase and urocanase. The inducible nature of this production indicated that the hut repressor gene also was present on this fragment. Insertional inactivation of the histidine ammonia-lyase and urocanase genes by the gamma-delta transposon has permitted location of these structural genes and has provided evidence that transcription proceeds from urocanase through histidine ammonia-lyase. Mapping of the 16-kilobase-pair Pseudomonas DNA segment with restriction enzymes and subcloning of additional portions, one of which contained the gene for formiminoglutamate hydrolase and another that could constitutively express activities for both imidazolone propionate hydrolase and formylglutamate hydrolase, has provided evidence for the organization of all hut genes.